2018
DOI: 10.1038/s41467-017-02612-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative optical nanophysiology of Ca2+ signaling at inner hair cell active zones

Abstract: Ca2+ influx triggers the release of synaptic vesicles at the presynaptic active zone (AZ). A quantitative characterization of presynaptic Ca2+ signaling is critical for understanding synaptic transmission. However, this has remained challenging to establish at the required resolution. Here, we employ confocal and stimulated emission depletion (STED) microscopy to quantify the number (20–330) and arrangement (mostly linear 70 nm × 100–600 nm clusters) of Ca2+ channels at AZs of mouse cochlear inner hair cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
132
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(137 citation statements)
references
References 75 publications
4
132
1
Order By: Relevance
“…In the mammalian cochlea, each IHC is contacted by 10-30 1 SGNs, whereby predominantly an AZ with a single ribbon drives firing in a single unbranched peripheral dendrite. These afferent connections exhibit great diversity in synaptic and 1 SGN dendritic morphology 1320 , physiological properties 6, 13, 16, 17, 20–24 , and molecular 1 SGN profile 2527 . What might appear as a peculiar biological variance at first glance, is becoming increasingly recognized as a fascinating parallel information processing mechanism by which the auditory system copes with encoding over a broad range of sound pressures downstream of cochlear micromechanics.…”
Section: Introductionmentioning
confidence: 99%
“…In the mammalian cochlea, each IHC is contacted by 10-30 1 SGNs, whereby predominantly an AZ with a single ribbon drives firing in a single unbranched peripheral dendrite. These afferent connections exhibit great diversity in synaptic and 1 SGN dendritic morphology 1320 , physiological properties 6, 13, 16, 17, 20–24 , and molecular 1 SGN profile 2527 . What might appear as a peculiar biological variance at first glance, is becoming increasingly recognized as a fascinating parallel information processing mechanism by which the auditory system copes with encoding over a broad range of sound pressures downstream of cochlear micromechanics.…”
Section: Introductionmentioning
confidence: 99%
“…In drosophila NMJ, super-resolution microscopy has demonstrated that VGCCs are arranged in a tight cluster (50 - 100 nm diameter) with vesicles being tethered around its perimeter (Liu et al, 2011). Recently at mouse inner hair cells super-resolution microscopy identified linear clusters of VGCCs (Neef et al, 2018; Wong et al, 2014) that in combination with VGCC cooperativity measurements and numerical simulations drive release from within ∼20 nm of the cluster perimeter (Pangrsic et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…To date specific VGCCs-SV topographies have been proposed at Drosophila (VGCC clusters coupled to vesicles around its perimeter) and mammalian NMJ (rows of VGCC and SVs), and at hair cell synapses (rows of calcium channels coupled to SV around its perimeter; Dittrich et al, 2013; Luo et al, 2015; Neef et al, 2018; Pangrsic et al, 2015). However, the nanoscale organization of SVs and VGCCs underlying the functional diversity of CNS synapses is less well understood.…”
Section: Introductionmentioning
confidence: 99%
“…In our experiments, the RRP is not affected in the IHCs from VGLUT3 A224V/A224V mice. In hair cells, the calcium channels are densely packed underneath the presynaptic element and the RRP correlates to the membraneproximal synaptic vesicles, i.e., the vesicles tether to the synaptic body and docked to the plasma membrane (Khimich et al, 2005;Schnee et al, 2005;Rutherford & Roberts, 2006;Meyer et al, 2009;Frank et al, 2010;Pangršič et al, 2010;Wong et al, 2014;Neef et al, 2018).…”
Section: Synaptic Plasticity In Vglut3 A224v/a224vmentioning
confidence: 99%